2008
DOI: 10.1097/ta.0b013e31817c9687
|View full text |Cite
|
Sign up to set email alerts
|

Age of Transfused Blood: An Independent Predictor of Mortality Despite Universal Leukoreduction

Abstract: Although larger volumes of blood, irrespective of age, are associated with increased odds of mortality, the transfusion of blood stored beyond 2 weeks appears to potentiate this association despite a practice of universal leukoreduction. For patients who receive relatively smaller transfusion volumes, blood age appears to have no effect on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
230
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(244 citation statements)
references
References 11 publications
9
230
4
1
Order By: Relevance
“…L2880, Sigma, Buchs, Switzerland) followed two hours later by intravenous (i.v.) injection of 5x10 8 or 1x10 9 RBC-MV in a total volume of 200µl PBS via the tail vain. At the indicated times, mice were sacrificed with thiopental and organs were harvested.…”
Section: Methodsmentioning
confidence: 99%
“…L2880, Sigma, Buchs, Switzerland) followed two hours later by intravenous (i.v.) injection of 5x10 8 or 1x10 9 RBC-MV in a total volume of 200µl PBS via the tail vain. At the indicated times, mice were sacrificed with thiopental and organs were harvested.…”
Section: Methodsmentioning
confidence: 99%
“…In September 2008, Weinberg and his colleagues reported on a review of 1813 trauma patients transfused at least 1 unit of red blood cells over a 7·5-year period [57]. The group performed by both contingency table and regression analysis of the relationship of numbers of units of long-stored red blood cells and mortality and found an association by regression but not in the contingency table analysis.…”
Section: Data From Clinical Studiesmentioning
confidence: 99%
“…Regulations in many countries specify 42 days (6 weeks) as the shelf life for stored red blood cells (RBCs), and a first-in-first-out inventory management approach is standard. Large-scale clinical studies involving 200-1800 patients indicated that patients transfused with older RBCs tend to have a higher risk of mortality than those receiving fresher RBCs [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%